Surveying colloid sedimentation by coplanar waveguides. (26th April 2016) - Duţu, C A; Vlad, A; Roda-Neve, C; Avram, I; Sandu, G; Raskin, J-P; Melinte, S
Abstract: By using coplanar waveguides, direct access to the dielectric properties of aqueous solutions of polystyrene beads with different diameters from 330 nm to 10 μ m is provided. The relative variation of the transmission parameter with respect to water is monitored, ranging from ∼ 3 % obtained for a 9.5% solution with 330 nm diameter beads to ∼22% for 10 μ m diameter particles at the same concentration. To highlight its applicability in biosensing, the technique was further employed to survey the clustering between biotin and streptavidin-coated beads. The transmission parameter displays a ∼50% increase for mixtures containing nine volumes of biotin and one volume of streptavidin-modified beads (4.5 ng μ l –1 of streptavidin) and reaches ∼400% higher values when equal volumes of biotin and streptavidin-coated beads (22.5 ng μ l –1 of streptavidin) were mixed.